PENCAIRAN BATUBARA LIGNIT DAN SUBBITUMINOUS DENGAN DUA SISTEM REAKTAN BERBEDA TANPA KATALIS DAN PELARUT - Artanto, Yuli; Hartiniati, Hartiniati (Badan Pengkajian dan Penerapan Teknologi, 2009)
This study of coal liquefaction in the absence of catalyst and solvent wasconducted. In this research a comparison of two different coals was carried out tosee characteristic of each coal on the liquefaction reaction. The effect ofhydrogen and CO/H2O were also checked to understand the mechanism of theprocess. Lignite or brown coal from Tanjung Enim and sub bituminous coal fromEast Kalimantan are used in this study. The results suggest that increase in coalrank from lignite to sub bituminous did not alter the conversion significantly.Surprisingly, the reduction in conversion of sub bituminous coal by its inorganicand mineral content noted for hydrogenation reactions (with added tetralin) is notobserved in CO/H2O reactions. For lignite, there is a tendency for conversion toincrease.Kata kunci: lignit, sub bituminous coal, non solvent hydrogenation